Cervical Spine Pathology Increases the Risk of Rotator Cuff Tear: A Population-Based Cohort Study. Issue 12 (9th December 2021) - Wang, Jr-Yi; Lin, Yu-Ru; Liaw, Chen-Kun; Chen, Chih-Hwa; Lin, Hui-Wen; Huang, Shih-Wei
Background: Patients with cervical radiculopathy typically present with shoulder pain and weakness; these symptoms are similar to those of rotator cuff disease. Studies investigating cervical spine pathology (CSP) as an independent risk factor for rotator cuff tear (RCT) are lacking in the literature. Purpose: To investigate the risk of RCT among patients with CSP who have undergone cervical diskectomy (CD) and to determine whether CD reduces this risk. Study Design: Cohort study; Level of evidence, 3. Methods: The authors queried the Taiwan National Health Insurance Research Database for patients diagnosed with CSP between 2004 and 2008 and followed up until the end of 2010. A control cohort comprised patients without CSP who were age- and sex-matched in a 4-to-1 ratio with patients with CSP through propensity score matching. A Cox multivariate proportional hazards model was applied to analyze the risk factors for RCT. After adjustment for confounders, the authors calculated the hazard ratio (HR) and adjusted HR (aHR) between the study and control cohorts. The effects of CD on the risk of RCT were also analyzed. Results: The study included 3245 patients and 12, 980 matched controls. A higher RCT incidence rate was found in the CSP cohort, with an aHR of 1.52 (95% CI, 1.22-1.89; P < .001). Patients with CSP who underwent CD had a risk of RCT similar to that of the controls, with an aHR of 1.65 (95% CI, 0.90-3.03; P > .05). Conclusion: Patients with CSP had a 1.52-fold higher risk of RCT than healthy controls. Patients with CSP with CD did not have a high risk of RCT, possibly indicating a protective effect of diskectomy against RCT.